Deforestación y pérdida de la diversidad de aves en la carretera Quistococha - Llanchama, Loreto - 2020 - Alvarez Vasquez, Luis Fernando (2021)
On the axis of the Quistococha-Llanchama highway, located in the district of San Juan Bautista, in the Loreto region, obviously, for different reasons the phenomenon of deforestation is occurring, which has as one of its effects the loss of bird biodiversity, so in this research work we asked ourselves the following question: To what extent is deforestation influencing the loss of bird diversity on the Quistococha-Llanchama highway? In order to answer this question, we set ourselves the followingobjective, "to know the degree of deforestation and the loss of bird diversity on the Quistococha-Llanchama highway". In order to know the degree of reforestation, satellite images were used, duly georeferenced at a scale of 1/100,000 from the years 2005, 2010, 2015 and 2018. The composition and abundance of bird diversity was determined using the linear transect method, for the capture of birds, 10 haze nets were used in each sampling (12 x 3.6 m: with stretched mesh diameter from 30 to 36 mm). Anthropic activities are closely linked to deforestation and consequently to the change in the composition of bird diversity on the Quistococha-Llanchama highway. The specific richness of birds (161 species) reported in the area is high. The results of the abundance indicate that there is a low density of the different species reported for the area.